2017
DOI: 10.29311/ndtps.v0i12.2332
|View full text |Cite
|
Sign up to set email alerts
|

Student perceptions of quality in higher education: effect of year of study, gender and ethnicity.

Abstract: Student expectations with regard to what comprises quality in higher education can impact upon their learning, engagement and overall satisfaction. Perceptions of quality are not always clearly articulated and may vary by gender, ethnicity and year of study. In this study, undergraduate students completed a questionnaire indicating whether they agreed, disagreed or were unsure about 15 statements related to quality in higher education. A total of 340 students across four year groups participated (Levels 3-6), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 15 publications
0
12
0
1
Order By: Relevance
“…In schools, the relationships between staff members feed into the culture and ethos of the school and thus have a major impact on student achievement (Barth, 2006). There is no reason to suppose it would be different in higher education, and in university students, relationships with academic staff are highly valued both as part of student belonging (Dwyer, 2017), and as a marker of institutional quality (Dicker et al, 2017(Dicker et al, , 2018. Ensuring that relationships may be nurtured without face-to-face contact will be a challenge, especially for new students starting in September with whom entirely new relationships need to be formed.…”
Section: Discussionmentioning
confidence: 99%
“…In schools, the relationships between staff members feed into the culture and ethos of the school and thus have a major impact on student achievement (Barth, 2006). There is no reason to suppose it would be different in higher education, and in university students, relationships with academic staff are highly valued both as part of student belonging (Dwyer, 2017), and as a marker of institutional quality (Dicker et al, 2017(Dicker et al, , 2018. Ensuring that relationships may be nurtured without face-to-face contact will be a challenge, especially for new students starting in September with whom entirely new relationships need to be formed.…”
Section: Discussionmentioning
confidence: 99%
“…Student partners identified being able to work closely with staff partners as one of the main reasons they got involved. Students have been shown to value relationships with academics most highly followed by interactions with their peers (Dicker et al, 2017), when identifying markers of what constitutes high quality higher education. The integration of staff research into undergraduate student teaching is quite commonplace in higher education, although undergraduate and postgraduate views on such can be both positive and negative (Lindsay et al, 2002).…”
Section: The Opportunity To Work Closely With Academic Staffmentioning
confidence: 99%
“…In this case, qualitative and quantitative responses suggested that students recognise the contribution of lecturers and teaching and learning provision to their overall experience, which is in agreement with others (Neves & Hillman, 2016). As in Dicker,et al,most (95%) of the students surveyed agreed with the statement that 'the lecturers I have an impact upon my learning' (Dicker et al, 2017).…”
Section: Discussionmentioning
confidence: 64%